Ø§Ù„Ø´Ø®Øµ Ø§Ù„Ø±Ø¦ÙŠØ³ÙŠ ÙÙŠ Ø§Ù„Ø±ÙˆØ§ÙŠØ© "Ø§Ù„Ø±Ø¬Ù„ Ø§Ù„Ø°ÙŠ Ø£Ù…Ù†" Ù„Ù†Ø¬ÙŠØ¨ Ø§Ù„ÙƒÙŠÙ„Ø§Ù†ÙŠ (Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© Ø³ÙŠÙƒÙˆÙ„ÙˆØ¬ÙŠØ© Ù„Ø£Ø¨Ø±Ø§Ù‡Ø§Ù… Ù…Ø§Ø³Ù„Ùˆ - durrotus shinta (AN-NAS, 2018)
"The Man Who Believes" the book of the novel Najib Kailani. This novel tells about the motives for the conviction of human needs. And about the man who believed in the way of women. The human psychological analysis in literature focuses on the texts of literature in which the image of the hierarchy of human needs, and uses the human psychological theory of Abraham Maslow is the Pyramid of Human Needs. The questions in this research are how the person and personality, and how the pyramid of needs in the main person in the novel "The Man Who Believes" to Najib Kailani. The objectives of research are to know the person and personality and to know the Pyramid of Human Needs in the main person in this novel. This research is qualitative research using the descriptive approach, and the process of analyzing the data is to read this novel and identify the person who relates to this research. The results of the research are led by the person, especially the main person, Erian and the Syams, and the analysis of the pyramid of the five needs. There is the physiological need, the security needs, the needs of love and conviction, the need for self-esteem and the needs of self-realization."